Post-Newtonian evolution of massive black hole triplets in galactic nuclei – IV. Implications for LISA. Issue 3 (28th March 2019) - Bonetti, Matteo; Sesana, Alberto; Haardt, Francesco; Barausse, Enrico; Colpi, Monica
ABSTRACT: Coalescing massive black hole binaries (MBHBs) of 10^4-7 M_, forming in the aftermath of galaxy mergers, are primary targets of the space mission LISA, the Laser Interferometer Space Antenna . An assessment of LISA detection prospects requires an estimate of the abundance and properties of MBHBs that form and evolve during the assembly of cosmic structures. To this aim, we employ a semi-analytic model to follow the co-evolution of MBHBs within their host galaxies. We identify three major evolutionary channels driving the binaries to coalescence: two standard paths along which the binary evolution is driven by interactions with the stellar and/or gaseous environment, and a novel channel where MBHB coalescence occurs during the interaction with a third black hole. For each channel, we follow the orbital evolution of MBHBs with physically motivated models that include a self-consistent treatment of the orbital eccentricity. We find that LISA will detect between ≈25 and ≈75 events per year depending on the seed model. We show that triple-induced coalescences can range from a few detected events up to 30 per cent of the total detected mergers. Moreover, even if the standard gas/stars-driven evolutionary channels should fail and MBHBs were to stall, triple interactions would still occur as a result of the hierarchical nature of galaxy formation, resulting in about ≈10 to ≈20 LISA detections per year. Remarkably, triple interactions among the black holes can produce coalescing binaries with large eccentricities (≳ 0.9) upon entrance into the LISA band. This eccentricity will remain significant (∼0.1) also at merger, requiring suitable templates for parameter estimation.